Crystal nucleation kinetics of a metastable phase on cordierite glass surfaces - Mora, N. D.; Zanotto, E. D.; Ziemath, E. C. [UNESP] (My University, 1996)
The crystal nucleation rates of a metastable phase (Χ) on the surface of a near stoichiometric cordierite glass were determined for temperatures between 839 and 910°C (Tg∼800°C). The surface nucleation kinetics of that phase on our glass, as well as on a stoichiometric glass (2MgO-2Al2O3-5SiO2) studied by other authors, were analysed in terms of the classical nucleation theory, for the first time. It was shown that the effective interfacial energy for surface nucleation is substantially lower than that for homogeneous volume nucleation in silicate glasses, vindicating the assumption of heterogeneous nucleation on free glass surfaces. The average wetting angle between the nucleating crystals and the active solid particles was estimated to be around 46°. The preexponential constant was several orders of magnitude higher than the theoretical values as found for volume homogeneous nucleation in oxide glasses.